العتبات النصية في رواية مرافئ الحب السبعة - شرايطة, إبراهيم (جامعة الوادي - university of Eloued, 2020)
تعد العتبات النصية مدخل الفهم النص إذ لا يمكن إستقراء النص بمعزل عن عتباته، بصفتها عاكسة لهواجسه والأفكار المطروحة في النص، فضلا عن كونها تشيب إماءات وتجليات لغوية عبر تكثيفها الثري الذي يغدو أكثر شعرية من المتن ذاته. وقد جاءت العتبات النصية في رواية مرافئ الحب السبعة متعالقة بالنص بتشابكية وطيدة لتثير أسئلة الوجود فضلا عن اضاءاتها للمتن من الداخل وإيضاحها عن إيديولوجيا الرواية حيث جسدت طروحاتها العلاقة الجدلية بين الأدب واللغة والفن والسرد مستفيدة من الرمزية، وهو ما سنحاول دراسته. The textual thresholds are an introduction to the understanding of the text, since the text cannot be interpreted far from its thresholds, because it reflects its concerns and ideas , as well as it reveals some connotations through its intensification which becomes more poetic than the text itself. The textual thresholds in the novel of the “Seven Love Harbors” are inextricably linked to the questions of existence, as well as its illumination of the inside, and its clarification of the ideology of the novel. Its issues have renewed The controversial relations between literature, language, art and narration. This article willtrytacklethese issues.
The textual thresholds in the novel Seven Love Ports
مقال
Keywords: العتبة؛ العنوان؛ الغلاف؛ الألوان